In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

In situ polymerization process: an essential design tool for lithium polymer batteries dagger - Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (Energy & Environmental Science, 2021)
Polymer electrolytes (PEs), a type of solid-state electrolytes (SSEs), have been in contention for nearly half a century to replace organic liquid electrolytes (LEs) that are used in state-of-the-art lithium-ion batteries (LIBs). They are envisaged to accelerate the industrial-scale production of safe, energy-dense, flexible, and thin lithium polymer batteries (LPBs). LPBs are expected to be widely employed for electric propulsion and other futuristic applications, such as flexible electronics and the Internet of Things (IoT). Even though several polymer architectures and chemistries have been attempted so far, PEs that can outperform LEs remain a real challenge. Apart from inadequate Li+-ion transport properties, challenges concerning the integration of PEs and the engineering of compatible, robust, and durable interfaces and interphases at both the electrodes of LPBs must be appropriately addressed. Recently, the in situ polymerization process has been widely employed as a robust fabrication tool for surpassing the intricacies related to the integration of PEs in LPBs. Hence, in this review, we focus on the in situ polymerization processes that employ various polymerization methods (e.g., free-radical polymerization, ionic polymerization, electropolymerization, condensation polymerization, etc.), functional monomers and oligomers (e.g., acrylate, methacrylate, allyl and vinyl ethers, epoxides, etc.), and PE integration strategies for the fabrication of lithium (ion and metal) polymer batteries (LIPBs and LMPBs). Additionally, this review also evaluates the approaches that have been developed until now to implement the in situ processing of LPBs from large-sized pouch cells to flexible-/printable-batteries and even microbatteries.

In situ preparation of ionomer as a tool for triple-phase boundary enhancement in 3D graphene supported Pt catalyst - Gangadharan, Pranav K.; Vijayakumar, Vidyanand; Nediyirakkal, Shijil A.; Fernandez, Roshni Tresa; Siddharthan, V. Adhrika; Kurungot, Sreekumar (Advanced Sustainable Systems, 2021)
For improving the performance of platinum electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs), it is important to enhance the Pt utilization level in the catalyst systems. A high performing electrocatalyst (Pt/3DNG) is developed for PEMFC applications by using nitrogen-doped 3D graphene (3DNG) as the support material and an in situ grafted active ``triple-phase boundary'' to more precisely control the formation of the proton conducting ionomer interface at the active sites. Considering the 3D morphology of the system, during the electrode fabrication for realistic single-cell evaluation, the concept of in situ generation of the proton conducting-ionomer based ``active triple-phase boundary'' is introduced, which could potentially replace the conventional method of using Nafion ionomer for the electrode preparation. The monomers owing to their small-size can access the pores and inner regions of the 3DNG support, which on UV-curing, undergo polymerization and transform into an ionomer with an extended interfacial network into the nanoregimes of 3DNG. Single cell evaluation of the membrane electrode assembly in a high-temperature PEMFC by using phosphoric acid doped polybenzimidazole membrane demonstrates the utility of the present strategy.
Keywords: electrocatalysts; fuel cells; graphene; oxygen reduction reaction

Interconnected polyaniline nanostructures: enhanced interface for better supercapacitance retention - Mooss, Vandana A.; Vijayakumar, Vidyanand; Kurungot, Sreekumar; Athawale, Anjali A. (Polymer, 2021)
Polyaniline and its nanocomposites have emerged as desirable electrode materials for supercapacitors. However, achieving specific capacitance with long-term cyclic stability is still a challenge. The present study reports on novel hierarchically porous and cross-linked polyaniline synthesized by a method employing aniline (monomer) and phytic acid (dopant acid) in the presence of octyltrimethyl ammonium bromide (OTAB) surfactant. The electrochemical performance of the phytic acid doped sample has been compared with HCl doped samples, the former being superior, i.e., a specific capacitance of 523 and 325 F g(-1) at current densities of 0.25 and 10 A g(-1), respectively. Additionally, the same possess excellent cycling stability with retention of similar to 88% of its initial capacitance over 10,000 charge-discharge cycles. Further, the phytic acid doped sample exhibited a lower equivalent series resistance (0.98 Omega cm(2)) than the HCl doped sample (1.26 Omega cm(2)). These results reveal the capability of the phytic acid doped hierarchical polyaniline sample as a promising active material for electrochemical applications.
Keywords: Cyclic stability; Hierarchical polyaniline; Supercapacitance retention

Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries